(untitled) (Research, Society and Development, 2020)
Objective: To characterize the scientific production of knowledge about public policies for the elderly in Brazil in the areas of health, violence, education and social assistance/participation. Method: scoping review, searching the databases of the VHL, CAPES, ERIC, PubMed, Redalyc and Scielo, since 2003, creation of the Elderly Statute, considering the descriptors ’public policy’, ’elderly’, ’aged’, ’older adults’, and their correspondents in Portuguese and Spanish, using the Boolean operators ’AND’ and ’OR’. Results: The search resulted in the selection of 21 articles aimed at the elderly in Brazil. The articles presented publications of public policies with little empirical methodologies and a lot of bibliographic research. The Elderly Statute and the Federal Constitution are the most commonly used legal documents in public policy studies. The areas of health, violence and social assistance have exclusive policies for the elderly, unlike the area of education. Conclusion: The scoping review identified different legal documentation for each area. It found a lack of homogeneity in the methodological aspects of the studies. This review can strengthen the studies on public policies for the elderly in Brazil, guiding the legal determinations of four areas: health, violence, education and social assistance / participation.